SKILL LEARNING ESTIMATE IN ELEMENTARY AGE SANTRI AT DARUL QUR'AN ISLAMIC BOARDING SCHOOL (DESCRIPTIVE ANALYSIS STUDY) - Jamalia, Jamalia; Lubis, Zulfahmi (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Listening skill or maharah istima' is one of the innate potentials for every human being from birth into the world. Likewise, this potential is very much in demand by students at the elementary age level. This study aims to describe the process of learning istima skills for elementary-age students at the Tahfidz Darul Qur'an Islamic Boarding School. This research is a type of qualitative descriptive study method, collecting data using observation, interviews, and documentation studies. The subjects of this study included students of class IX MTs at the Tahfidz Darul Qur'an Islamic Boarding School for the 2022/2023 academic year. The results of this study concluded that the learning process in Islamic boarding schools was good in improving students' istima' skills. This can be described since before entering class the teacher has prepared the material to be delivered and arranges giving assignments to the students starting from the students writing in their respective notebooks the important points that have been learned that day, the media used are visual and audio and The curriculum used is the independent curriculum. By using visual and audio media, it is more interesting for students to take part in istima skills learning in that class.